Some Aspects Of Ensuring Public Control In State And Social Management (Eurasian Journal of Humanities and Social Sciences, 2025)
This article analyzes the organizational and legal foundations of public control over the activities of government agencies.It is also said that the development and improvement of public control over the activities of state bodies with the participation of members of society in the management of state and society affairs is carried out on a constitutional and legal basis